PENERAPAN METODE DRILL DALAM PEMBELAJARAN BAHASA ARAB UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA KELAS IV MADRASAH IBTIDAIYYAH UYUN AL-HIKAM PRAJEGAN PONOROGO TAHUN AJARAN 2018/2019 - Arif Safrianto; Ahmad Muslich; Sigit Dwi Laksana (TARBAWI:Journal on Islamic Education, 2019)
The research background was based on observations at MI Uyun Al-hikam Prajegan, Sukorejo Ponorogo, the quality of Arabic language learning was still under the KKM The research aims to find out there is an effect of the application of the drill method to the results of Uyun Al-Hikam's fourth grade students' learning achievement. This research is Classroom Action Research (CAR) as the object of research is fourth grade students of MI Uyun Al-hikam in the form of cycle research procedures referring to four components including planning, acting observing, and reflecting and the data collection techniques use observation and tests. The results showed that the use of the drill method in Arabic language lessons could improve student learning based on the recapitulation of student test the results from cycle 1 and 2 percentage of KKM students increased to 75% which previously only 50% and from 75% only 3 students had not yet reached KKM value is 71 out of 12 students.